Molar incisor hypomineralization and oral health-related quality of life in Brazilian children: A narrative review of current evidence (Research, Society and Development, 2023)
The aim of this narrative review was to explore the association between Molar Incisor Hypomineralisation (MIH) and Oral Health-Related Quality-of-Life (OHRQoL) in Brazilian children aged 8-10 years. The study was developed considering the PRISMA guidelines (2020). Five databases were consulted to identify potential studies that used clinical parameters for the detection of MIH; and (b) studies that described aspects of the experience and severity of MIH; (c) records that adopted instruments recommended in the literature to explore OHRQoL in children, according to their respective age groups. The risk of bias of the included studies was analyzed using the Newcastle-Ottawa scale for the assessment of the quality of nonrandomized studies. Of the 155 initially found, three were included. Of these, two were cross-sectional and one was a case-control study.  The diagnosis of MIH was made according to the criteria of the European Academy of Paediatric Dentistry, and OHRQoL was identified using the Child Perceptions Questionnaire (CPQ8-10). The qualitative synthesis of the findings shows that no statistically significant association was identified between MIH and OHRQoL. Only the "oral symptoms domain" of the CPQ8-10 was associated with MIH. The studies were classified as having a low risk of bias (mean: 6.6★/7★). Thus, this study concluded that no significant association was identified between MIH and OHRQoL in Brazilian children. However, MIH may have a negative effect on the perception of oral symptoms in this population group.